"Paying it forward": The link between providers' civility climate, civility toward patients and patient experience outcomes. Issue 2 (April 2020) - Oppel, Eva-Maria; Mohr, David C.
Abstract : Background: Interpersonal relationships are increasingly recognized as an important determinant for care performance and quality in the health care context. An unresolved issue in health care research is whether and to which extent providers' perceptions of their work relationships are associated with their interactions with patients and, in turn, patient experience outcomes. Purpose: The aim of this study was to investigate the extent to which nurses' experiences of their work relationship climate (i.e., civility climate) affect their interactions with patients (i.e., civility towards patients), which in turn contribute to patient experience outcomes (i.e., overall hospital rating, willingness to return, intent to recommend). Furthermore, we analyze the mediating role of civility toward patients in the relation between civility climate and patient experience outcomes. Methodology: The 2011 study sample comprised responses from 6, 019 nurses and 38, 619 patients at 123 Veterans Health Administration acute care inpatient hospitals located in the United States. We developed and empirically tested a theoretical model using multilevel regression modeling and assessing multilevel mediation. Results: The results indicate a positive association between civility climate and civility toward patients. With regard to patient experience outcomes, the analyses reveal a direct effect of civility climate on overall hospital rating, intent to recommend, and willingness to return and an indirect effect mediated by civility toward patients. Conclusion and Practice Implications: This is one of the first studies theorizing and testing the extent to which relationship climate among providers affect their interactions with patients. The findings provide support that providers who experience a positive civility climate are more likely to pay forward this relationship experience and engage in civility toward patients. The results point to the importance of a civility climate for ensuring and potentially improving patient experience of care.